Molecular characterization of the Ftz‐f1 gene in redclaw crayfish Cherax quadricarinatus and its potential role in ovarian development. (10th August 2022) - Chen, Leran; Zheng, Jianbo; Jia, Yongyi; Li, Fei; Gu, Zhimin; Chi, Meili; Cheng, Shun; Liu, Shili; Jiang, Wenping; Liu, Yinuo
Abstract: Ftz‐f1 was a member of the NR5A‐family nuclear receptors, and previously predicted to be participated in the complex ovarian processes. In this study, we characterized the full‐length cDNA of Ftz‐f1 with an open reading frame of 1746 bp encoding 581 amino acids in the redclaw crayfish, Cherax quadricarinatus ( CqFtz‐f1 ). Amino acid alignments and structural prediction uncovered that two highly conserved domain, DBD (DNA binding domain) and LBD (ligand binding domain) were identified, which shared with other members of nuclear receptors family. Tissues distribution showed that CqFtz‐f1 exhibited sexually dimorphic expression pattern with a higher transcript level in ovary. Staging of ovarian development was conducted, which to be divided into four different stages by external feature and histology analysis. The changes of GSI (Gonadosomatic index) were in accordance with the mRNA expression of CqFtz‐f1 during the reproductive cycle. In addition, both eyestalk ablation and β‐oestradiol (E2) injection significantly increased the expression levels of Ftz‐f1 and vg (vitellogenin). Furthermore, treatment with CqFtz‐f1 dsRNA injection generated distinct effects on the expression of vg, suggesting that CqFtz‐f1 might have positive effects on ovarian development by regulating vg expression in the redclaw crayfish.